(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Oksana A. Maltseva (Kaliningrad, Russian Federation) Features of the lyrical subject in B. Pasternak’s cycle “Split” (from the book of poems “Themes and variations, 1916-1922”) are considered. It is argued that the leading problem is the definition of the lyric character of his/ her position with respect to the evil that prevails in the world: whether to follow the duty of a Christian whose conscience calls for combating evil or whether the voice of carnal fear requires reconciliation with evil and adapts to it. The specificity of the character’s spiritual choice is shown, where he/ she is in any case involved in a decisive conflict: on the one hand, tolerance for evil turns into a loss of conscience, a break with it, and therefore is a conscious step towards spiritual death; on the other hand, intransigence to evil turns into a quiet conscience, but a break with the world in which the character realizes himself doomed to physical harm. According to the author of the article, the title of the cycle “Split” reflects all the painful acuteness of the lyrical character’s choice. As an important semantic element, special attention is paid to historical and cultural allusions in the work of B. Pasternak. Key words: B. Pasternak, cycle, plot, lyric character, allusion. DOI 10.23683/1995-0640-2018-1-12-20